Ultrastructural characteristics of black marsh turtle spermatozoa obtained by electroejaculation. (19th July 2020) - Kimsakulvech, Sakdichod; Suttiyotin, Peerasak
Abstract: The black marsh turtle (Geoemydidae: Siebenrockiella crassicollis ) is a freshwater turtle that occurs in equatorial tropical climates in South East Asia. The semen of S. crassicollis was investigated by electroejaculation. The spermatozoa of S. crassicollis are filiform in shape with curved heads. The entire length, midpiece to tail length, tail width and tail length of the spermatozoa were 71.33 ± 1.55 μm, 49.92 ± 1.13 μm, 0.43 ± 0.02 μm and 48.53 ± 0.25 μm, respectively. The head length, head width across the middle and head width across the base were 14.00 ± 0.38 μm, 0.79 ± 0.03 μm and 0.91 ±0.0.03 μm, respectively. The acrosomal region of the S. crassicollis spermatozoa was narrower than the head, with an acrosomal length and width at the annulus of 2.90 ± 0.13 μm and 0.43 ± 0.01 μm, respectively. The midpiece of the S. crassicollis spermatozoa was narrower than the head and contained 30–40 mitochondrial balls, each with a ball diameter of 0.16 ± 0.002 μm. The midpiece length, midpiece width and tail length were 4.92 ± 0.16, 0.78 ± 0.03 and 48.53 ± 0.25 μm, respectively. This study presents the characteristic appearance of a freshwater turtle spermatozoa in Southeast Asia, as observed under an electron microscope. The spermatozoa of Siebenrockiella crassicollis are morphologically different from those of other freshwater turtles from other regions described in previous studies.